Peran Geografi Pembangunan Dalam Mewujudkan Pembangunan Berkelanjutan di Jawa Barat - Tia Setiawati; Siti Fadjarajani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Sustainable development is a crucial issue in efforts to improve community welfare without sacrificing environmental sustainability and the well-being of future generations. Development geography, with its spatial, ecological, and regional complex approaches, plays a strategic role in directing development to be more planned, equitable, and environmentally sound. This study uses a literature review method by examining various relevant literature sources regarding the dynamics of development in West Java. The results of the study indicate that West Java, as the province with the largest population and rapid economic growth, faces serious challenges in the form of urbanization, land conversion, environmental degradation, and inter-regional disparities. Development geography contributes by providing solutions through spatial analysis, spatial planning, and inter-regional integration to create equitable and sustainable development. Thus, the integration of development geography into regional policies is a crucial step towards realizing sustainable development in West Java.